Enriching the oral vocabulary of the educable mentally retarded primary level - Socrates, Vera Joy U. 1952-
The study answers the question on how to enrich the oral vocabulary of the educable mentally retarded in the primary level. It attempts to know the learning characteristics of the educable mentally retarded children, the implications of the learning characteristics to the enrichment of the oral vocabulary of the educable mentally retarded children, the objectives of oral vocabulary building for the educable mentally retarded children in the primary level, and the activities and experiences necessary to enrich the oral vocabulary of the educable mentally retarded children.